Cost of Responding to the 2017 University of Washington Mumps Outbreak: A Prospective Analysis. Issue 2 (March 2020) - Pike, Jamison; Schwartz, Sheryl; Kay, Meagan; Perez-Osorio, Ailyn; Marin, Mona; Jenkins, Mark; Routh, Janell; Duchin, Jeff; DeBolt, Chas; Zhou, Fangjun
Abstract : Objectives: To estimate costs of labor and materials by the University of Washington (UW) and state and local public health departments (PHDs) to respond to the February to June 2017 UW mumps outbreak, where 42 cases were identified among students (primarily sorority and fraternity members), staff, and associated community members. Design: We applied standard cost analysis methodology using a combined public health and university perspective to examine the cost of responding to the outbreak. Setting: UW's Seattle campus encompasses 703 acres with approximately 32 000 undergraduate students. Nearly 15% of the undergraduate population are members of fraternities or sororities. Housing for the fraternities and sororities is adjacent to the UW campus and consists of 50 houses. Participants: During the outbreak, customized costing tools based on relevant staff or faculty positions and activities were provided to the UW and Public Health–Seattle & King County, populated by each person participating in the outbreak response, and then collected and analyzed. Laboratory hours and material costs were collected from the Washington Department of Health and the Minnesota Department of Health. Main Outcome Measure: Labor and material costs provided by the UW and PHDs during the outbreak were collected and categorized by payer and activity. Results: Total costs to the UW and PHDs in responding to the outbreak were $282 762 ($6692 per case). Of these, the UW spent $160 064, while PHDs spent $122 098. Labor accounted for 77% of total outbreak costs, and UW response planning and coordination accounted for the largest amount of labor costs ($75 493) overall. Conclusions: Given the current university and public health department budget constraints, the response to the outbreak amounted to a significant use of resources. Labor was the largest driver of costs for the outbreak response; UW labor costs—related to campus response planning and coordination—dominated the total economic burden from public health and university perspectives.